2020
DOI: 10.3390/ijms21061910
|View full text |Cite
|
Sign up to set email alerts
|

NR2F2 Orphan Nuclear Receptor is Involved in Estrogen Receptor Alpha-Mediated Transcriptional Regulation in Luminal A Breast Cancer Cells

Abstract: Nuclear Receptor Subfamily 2 Group F Member 2 (NR2F2) is a member of the steroid/thyroid hormone receptor superfamily with a crucial role in organogenesis, angiogenesis, cardiovascular development and tumorigenesis. However, there is limited knowledge about the cistrome and transcriptome of NR2F2 in breast cancer. In this study, we mapped the regulatory mechanism by NR2F2 using functional genomic methods. To investigate the clinical significance of NR2F2 in breast cancer, The Cancer Genome Atlas (TCGA) data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…The antiproliferative effects of tamoxifen are enhanced by COUP-TFII overexpression ( 68 ). Similar to other corepressors, the expression of NR2F2 is also decreased in tamoxifen resistance ( 73 ).…”
Section: Endocrine Resistancementioning
confidence: 99%
“…The antiproliferative effects of tamoxifen are enhanced by COUP-TFII overexpression ( 68 ). Similar to other corepressors, the expression of NR2F2 is also decreased in tamoxifen resistance ( 73 ).…”
Section: Endocrine Resistancementioning
confidence: 99%
“…Previous studies have shown that NR2F2 expression was positively correlated with cell invasion, migration, and the expression of N-cadherin and vimentin [ 33 ] and has a key role in ERα-mediated transcription [ 34 ]. NR2F2 can also promote tumor cell proliferation, epithelial-mesenchymal transition, and invasive characteristics and inhibit tumor differentiation and immune cell infiltration by regulating transcriptional programs commonly found in mouse and human squamous cell carcinomas [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have validated the fact that miR‐144‐3p expression suppresses NR2F2 expression. NR2F2 is a steroid/thyroid hormone receptor with a crucial function in angiogenesis, organogenesis, cardiovascular development, and tumorigenesis 18,19 . NR2F2 upregulation accelerates cell proliferation 20 .…”
Section: Discussionmentioning
confidence: 99%